The Diversity Distribution and Climatic Niche of Samara Species in China - Du, Yanjun; Zhao, Yuan; Dong, Shupeng; Chen, Guoke; Wang, Xinyang; Ma, Keping (Frontiers in Plant Science, 2022)
Studying the distribution of samara species is of ecological and economic significance. This information helps us with understanding species dispersal mechanisms, evaluating the risk of invasive species, and the management of ecological forests. However, limited research has explored, on a large scale, the geographic distribution of samara species and their influential abiotic factors. Here we use the distribution data of 835 vascular samara species and growth form data to explore their geographic patterns in China and the environmental determinants. We divided China into 984 grid cells and examined the relationship between the proportion of samara species and climate variables using both ordinary and spatial linear regressions for each grid cell. Total samara species richness is higher in southern China in low altitude regions and the proportion of woody samara species is significantly higher than that of herbaceous samara species. The proportion of woody samara species is higher in the northeast regions where precipitation is sufficient, winters are dry and mild, and temperature seasonality and land surface relief degree values are high. Annual precipitation and temperature seasonality are the most important climate drivers for the distribution of woody samara species. In contrast, herbaceous samara species prefer to distribute to the areas where climate is warm and dry but have higher temperature seasonality. Temperature related variables (mean annual temperature, mean diurnal range, and temperature seasonality) are the most important drivers for the distribution of herbaceous samara species. Samara species can better adapt to climatic regions with large temperature fluctuations and dry winters. The present distribution patterns of samara species are formed by the combined adaptation of fruit traits and growth form to climate. This work contributes to predictions of the global distribution of samara species under future climate change scenarios and conservation and management for the samara species.